AKTIVITAS AKAL DALAM PEMBUKTIAN KEBENARAN WAHYU - Sidik Ibrahim (Hunafa: Jurnal Studia Islamika, 2007)
This article elaborates reason activities to understand and to prove a reason truth. Philosophers always endeavor to use their reasons to obtain a truth through revelation so that a rational and scientific truth can be obtained. It is within this context that to understand revelation, reason is needed to prove the truth. Based on both Muslim philosophers’ and non- philosophers’ systematical and careful thoughts, the Qur’an has allotted many contributions to the development of both science and human civilization.Kata Kunci: Aktivitas akal, kebenaran wahyu